Wage distortion and green technological progress: A directed technological progress perspective - Yang, Zhenbing; Shao, Shuai; Fan, Meiting; Yang, Lili (Ecological economics, 2021)
In this paper, we construct a theoretical model considering that wage distortion is exogenous and endogenous, respectively, to explore the effect of wage distortion on green technological progress. Furthermore, using the panel data of China's industrial sector, we investigate the direct influence and mediating effect of wage distortion on green technological progress. We find that the green technological progress of China's industrial sector continued to rise from 2002 to 2012. However, the green technological progress of China's manufacturing sub-sectors is relatively slow. The wage distortion phenomenon that the labor's real wage level is less than the labor's marginal product level is widespread, especially in manufacturing sub-sectors. Moreover, green technological progress has a path-dependence characteristic. Wage distortion plays an important role in the changes in the direction of green technological progress. Green technological progress is more likely to appear in the sub-sectors which experience low wage distortion degree, while the sub-sectors with severe wage distortion experience a lower green technological progress rate. Wage distortion increases industrial profit margins by deliberately suppressing the rise of wages. In addition, increased industrial profit margins reduce the incentives of the green technological innovation of equipment suppliers and inhibit the improvement in green production technology. Therefore, alleviating wage distortion can benefit the green development of industrial sector.